Vitamin-D deficiency impairs CD4þT-cell count recovery rate in HIV-positive adults on highly active antiretroviral therapy: Q9 A longitudinal study - Ezeamama, A.E.; Guwatudde, D.; Wang, M.; Bagenda, D.; Kyeyune, R.; Sudfeld, C.; Manabe, Y.C.; Fawzi, W.W. (Clinical Nutrition, 2015)
We implemented a prospective study among human immunodeficiency virus (HIV)- positive adults to examine the association between vitamin-D deficiency (VDD) and insufficiency (VDI) vs sufficiency (VDS) and CD4þT-cell improvement over 18 months of highly active antiretroviral therapy (HAART). Methods: We used data from a randomized placebo-controlled micronutrient trial with 25-hydroxy vitamin-D (25(OH)D) measured at enrollment in 398 adults. CD4þT-cell count was measured repeatedly at months 0, 3, 6, 12 and 18. Linear mixed models quantified the vitamin-D-related differences in CD4þT-cell count and associated 99% confidence intervals at baseline and respective follow-up intervals. Results: At baseline 23%, 60% and 17% of participants were VDS, VDI and VDD, respectively. Absolute CD4þT- cell counts recovered during follow-up were persistently lower for baseline VDD and VDI relative to VDS participants. The greatest deficit in absolute CD4þT-cells recovered occurred in VDD vs VDS participants with estimates ranging from a minimum deficit of 26 cells/ml (99% CI: 77, 26) to a maximum deficit of 65 cells/ml (99% CI: 125, 5.5) during follow-up. This VDD-associated lower absolute CD4þT-cell gain was strongest among patients 35 years old or younger and among participants with a baseline body mass index of less than 25 kg/m2. Conclusions: VDD is associated with lower absolute CD4þT-cell count recovery in HIV-positive patients on HAART. Vitamin-D supplementation may improve CD4þT-cell recovery during HAART. However, future intervention studies are needed to definitively evaluate the effectiveness of this vitamin as an adjunct therapy during HAART.
Keywords: Vitamin-D; HIV; CD4þ; T-cell count; Antiretroviral therapy; Immune recovery